Analisis Perbandingan Fonologi Bahasa Indonesia dan Bahasa Melayu dalam Kartun Omar dan Hana - Hana Nurhasanah; Agi Ahmad Ginanjar (Bhinneka: Jurnal Bintang Pendidikan dan Bahasa, 2024)
This study aims to compare Indonesian and Malay in terms of phonology, with the cartoon series “Omar and Hana” as the research subject. Judging from the existing reality, Indonesian and Malay are two cognate languages that have many similarities, both in terms of grammar, vocabulary, and pronunciation. However, Indonesian and Malay also have differences, especially in terms of phonology. Therefore, this research tries to dig deeper into the comparison of phonology between Indonesian and Malay. The method used is descriptive qualitative with free listening and spoken involvement techniques and using writing techniques in data collection. The researcher found phonetic elements in Malay that aired on one of the themes in episode one, namely family themes. It was found that these two languages have almost similar functions of duration, stress, tone and stop in the pronunciation of vocabulary. However, there are differences, such as the sengau sound which is more distinctive in Malay. In addition, there is a change of vowel 'a' to 'ə' in some existing words that have the same meaning and arrangement pattern. This results in the existence of vocabulary whose sentences are different but the meaning is the same between Indonesian and the discovery of similar words but different meanings.